Total quality management : mastering your small business - Rossiter, Jill.; Chartered Institute of Bankers (London : The Chartered Institute of Bankers, 1998)
Leads the learner through the process of mastering the business concepts necessary to a successful small business owner or manager.
Originally published: Chicago, Ill. : Upstart Pub. Co., 1996.
Includes bibliographical references and index.
oif 31/03/15
Loan
Keywords: Small business; Total quality management